Effectiveness of positive parenting method on affective-behavioral difficulties of primary school children with learning disorders (disability) - Golnar Amirtahmaseb; Fariborz Bagheri; Khadijeh Abolmaali (مجله علوم روانشناختی, 2018)
Background: The family is the first and most durable factor that has been known as the constructor of the character of the next child's behaviors. Aims: The objective of present research is to study the effectiveness of positive parenting style on affective-behavioral difficulties of primary school children with learning disorders. Method: The present research design is from semi-experimental type. Statistical population of this research consists of all students with learning disability in primary level referring to Araman Counseling Center in 2017 in order to recover from this problem. Sample includes 39 students who were selected purposefully, according to inclusion and exclusion criteria, and divided randomly to two groups each including 16 students; they were evaluated pre and post intervention, by research tool. The research tool was Rotter’s affective-behavioral problems checklist. Research data was analyzed by mixed analysis of variance. Results: Data analysis results showed that, in 3 stages of evaluation, th ere were significant differences between violence and hyperactivity, anxiety and depression, social incompatibility and antisocial behavior averages of participants according to their membership in positive parenting style and control group(P<0/05). Conclusions: So, we may conclude that positive parenting style influences affective-behavioral problems of primary school children with learning disorders.